INTEGRATED USE OF NEOCHETINA BRUCHI AND ALTERNARIA EICHHORNIAE IN CONTROLLING WATER HYACINTH - OKKY S. DHARMAPUTRA; KASNO KASNO; SUNJAYA SUNJAYA; ASMARINA S.R. PUTRJ; HERI S. HANDAYANI (SEAMEO BIOTROP, 1999)
The study on the integrated use of the chevroned water hyacinth weevil (Neochetina bruchi Mustache) and the water hyacinth blight diseaseÂ (Alternaria eichhorniae Nag Raj & Ponnappa) in suppressing water hyacinth growth was carried out under field conditions at Situ Bagendit lake, Garut, West Java. The objectives of this study were (I) to investigate whether the combined use of the two control agents produced a better effect in suppressing water hyacinth growth, (ii) to evaluate whether there is a change in oviposition and feeding habit of the chevroned water hyacinth weevil if the water hyacinth is seriously infected byÂ A. eichhorniae, and (iii) to evaluate the progress of weevil establishment in the field. The following results were obtained:(1) The concentration of Tween 80 which did not interfere with spore germination was 3%.(2) There was no difference between distilled water and 1% Potato Dextrose Broth (PDB) as a medium for fungal spores production.(3) The combined use of chevroned water hyacinth weevil and the water hyacinth blight produces a better suppressing on water hyacinth growth.(4) There was no significant effect of heavy infection by the water hyacinth blight on oviposition habit of chevroned water hyacinth weevil. Heavy fungal infection only affected feeding habit of the adult chevroned water hyacinth weevil.(5) Establishment of the chevroned water hyacinth weevil is in progress at Situ Bagendit lake, Garut regency, West Java.